AhR‐Dependent Induction of β‐Defensin 1 in Colonic Epithelial Cells Regulates Cross‐Talk between Gut Microbiota and Immune Response Leading to Attenuation of Colitis - Manikandan Palrasu; Amarnath Marudamuthu; Khadija Kakar; Hamida Hamida; Shruthi Thada; Rohan Gupta; Kiesha Wilson; Taylor Carter; Yin Zhong; Archana Saxena; Xiaoming Yang; Narendra Singh; et al. (Advanced Science, 2025)
Abstract The aryl hydrocarbon receptor (AhR) acts as a critical signaling hub that connects immune cells, food and environmental cues, and microbiota to regulate intestinal homeostasis. In the current study, the role of AhR in the regulation of an antimicrobial peptide, β‐defensin1 (BD‐1) is investigated to control colitis. Human patients with ulcerative colitis (UC) and Crohn's disease (CD), and mice with three different models of colitis, express a significant decrease in the expression of BD‐1 in colonic epithelial cells (CECs). Dietary and environmental AhR ligands induce the expression of BD‐1 in CECs through the activation of two dioxin‐responsive elements (DREs) expressed on its promoter. AhR ligands attenuate colitis in wild‐type (WT) mice while inducing BD‐1. However, AhR ligands fail to induce BD‐1 and protect mice from colitis when there is an intestinal epithelial cell (IEC)‐specific deletion of AhR. Blocking BD1 in vivo using antibodies prevents the ability of AhR ligands to ameliorate colitis, restore dysbiosis, and attenuate colonic inflammation. The current study identifies a novel pathway involving dietary, environmental, and endogenous AhR ligands to induce the antimicrobial peptide BD‐1 in IECs, which in turn, plays a critical role in the regulation of intestinal homeostasis.